2021
DOI: 10.47626/2237-6089-2020-0143
|View full text |Cite
|
Sign up to set email alerts
|

Association between Big Five personality factors and medication adherence in the elderly

Abstract: Introduction Adherence to medications can be associated with circumstances related to the patient, with the pathology, with cultural health beliefs, with habits, and with quality of life. Behavioral patterns can also directly influence a patient’s pharmacological adherence, since they are related to their perception and understanding of their own health status and of their drug and non-drug treatments. Objective To investigate the association between adherence to pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(33 reference statements)
0
7
0
Order By: Relevance
“… 39 , 40 More specific examination of personality characteristics of the Big Five Inventory personality traits (Agreeableness, Conscientiousness, Extraversion, Neuroticism, and Openness) suggested that neuroticism was the characteristic to most likely correlate with the psychosocial aspects of HRQOL. 36 There is also evidence that this personality trait is negatively associated with medication adherence in elderly people 41 and in people with type 2 diabetes, 42 whereas both agreeableness and conscientiousness are positively related to medication adherence. 43 Neuroticism was also found to be negatively associated with lifestyle (exercise and diet) in people with type 2 diabetes, 44 conscientiousness being found be associated with the practice of self-monitoring of blood glucose and medication adherence in people with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 More specific examination of personality characteristics of the Big Five Inventory personality traits (Agreeableness, Conscientiousness, Extraversion, Neuroticism, and Openness) suggested that neuroticism was the characteristic to most likely correlate with the psychosocial aspects of HRQOL. 36 There is also evidence that this personality trait is negatively associated with medication adherence in elderly people 41 and in people with type 2 diabetes, 42 whereas both agreeableness and conscientiousness are positively related to medication adherence. 43 Neuroticism was also found to be negatively associated with lifestyle (exercise and diet) in people with type 2 diabetes, 44 conscientiousness being found be associated with the practice of self-monitoring of blood glucose and medication adherence in people with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Higher conscientiousness often represents the ability to be prudent, responsible, and self-controlled ( 18 ). A study indicated that higher conscientiousness was accompanied by higher adherence to adapting to healthy behaviors ( 49 ). Therefore, older people with higher conscientiousness would pay more attention to their health and actively prevent falls.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence may also be associated with individual characteristics of older persons, such as cognitive function, vision loss, lack of understanding, inability to administer several medications, and personality. 28 Patient adherence to medications is assessed using the TAM, with the authorization of the authors. TAM is a free tool that can be administered quickly and consists of 7 easy-to-understand questions.…”
Section: Discussionmentioning
confidence: 99%